The Acts of the Apostles [electronic resource] : translated into the language of the Esquimaux Indians on the coast of Labrador - Moravian Church.; British and Foreign Bible Society. (London : Printed by W. M'Dowall, ., 1816)
"Printed at the expense of the British and Foreign Bible Society." Electronic reproduction. Mode of access: Internet. 44